Government policy in human capital accumulation and technology transfer - Tadesse, Kuma Worako (KDI School, 1998)
Korea has achieved remarkable economic growth in the last three-to-four decades. Its economy transformed from poor agrarian level to world industrial nation within a short period. Many scholars have different views in explaining how this miraculous development occurred. However, there are some stylized facts that all agree with out difference. These facts include the government policies that put prime importance on the development of human capital, outward-looking growth strategy and the acquisition of foreign technologies through trade and the strong institutions adopted by government; each of which reinforce each other. In the early 1960s, even before the economic take off, Korea had a well-educated labor force. 1bis increased the success in export promotion development strategy and conversely trade increased the demand for human capital, thereby increasing the return from its investment. This study attempted to explore the government policies that contributed to rapid success in expansion of human capital and technology transfer. And the relation between per capita income growth, availability of threshold human capital, and outward-looking growth strategy. The result for empirical estimation made using time series data for period 1963 to 1993, shows that they have positive and strong relation. The same estimation made for seven high performing East Asian economies show also the same association. This all depicts that early investment in people is more profitable than any other investment in elsewhere.
Thesis(Master) --KDI School:Master of Growth and Development Studies,1998